Pelaksanaan Kampus Mengajar di Daeah 3T: Program Asistensi Mengajar Fakultas Keguruan dan Ilmu Pendidkan Universitas Pendidikan Muhammadiyah Sorong di SD Negeri 3 Kabupaten Sorong Semester Ganjil Tahun Akademik 2021/2022 - budi santoso; Jusmin Jusmin; Muhammad Muzakki; Mukhlas Triono; Fathurrahman Fathurrahman (Universitas Pendidikan Muhammadiyah Sorong, 2023)
This service is motivated by the Teaching Campus activity which is a form of implementing the Merdeka Learning Campus Merdeka (MBKM) teaching assistance program at the Muhammadiyah Education University Sorong to empower students in helping the learning process in elementary and junior high schools in Sorong Regency. in the form of direct teaching, preparing Learning Device Plans and learning media for school administration. The end result of this activity is that this program is based on not being fully effective. This can be seen from the lack of students who have the opportunity to hone their interpersonal and leadership skills during teaching assistance activities. Routine activities are teaching in class, making learning media as well as when on duty as pickets and adapting technology.